The Effects of Moxifloxacin on QTc Interval in Healthy Korean Male Subjects - Moon, Seol Ju (Springer International Publishing, 2014)
BACKGROUND AND OBJECTIVE: Moxifloxacin 400 mg is a widely used positive control in thorough QT (TQT) studies, but its QT-prolonging effects in Korean subjects have not been studied. The present study was conducted to collect pilot data in Korean subjects after moxifloxacin administration to evaluate the adequacy of moxifloxacin as a positive control. METHODS: Thirty-eight, healthy, Korean, male subjects were recruited for pharmacokinetic (PK) blood sampling and electrocardiography (ECG) recordings at three different study sites. On day 1, a baseline 12-lead ECG was recorded, and on day 2, ECG recordings were conducted after placebo, or moxifloxacin 400- or 800-mg administration. Baseline-corrected, placebo-adjusted, corrected QT (ΔΔQTc) values were calculated. Blood samples were collected after moxifloxacin administration and PK parameters were assessed. RESULTS: A total of 33 subjects completed the study. The largest time-matched ΔΔQTc occurred approximately 4 h after dosing, with ΔΔQTcI (QT interval corrected by individual QT-RR regression model) values of 11.66 ms (moxifloxacin 400 mg) and 20.96 ms (800 mg). The mean and 90 % confidence intervals of ΔΔQTcI did not include zero at any of the measurement time points. There was a positive correlation between plasma moxifloxacin concentration and ΔΔQTcI (r = 0.422). Dose-proportional PK profiles were observed. CONCLUSION: Moxifloxacin 400 mg is an adequate positive control in Korean TQT studies. Our results indicate that moxifloxacin 400 mg can be used to evaluate the cardiac safety of a drug in Korean subjects.